Design of a Solar powered Groundnut Oil Expelling. - Mugumya Syrus (Kabale University, 2023)
Groundnut is an important food crop that serves numerous food purposes. Extracting oil from the seed, is key to its vast applications. In an attempt to ease the bottleneck in crushing the seeds to release the oil for utilization, a solar powered groundnut expelling machine is needed to efficiently squeeze various sizes of groundnut seeds. The essential components of the expelling machine are the hopper, the extracting chamber unit, the screw shaft unit, the frame and the power unit. Its design and operation are based on the engineering properties of the groundnut seed.